Pengaruh Kepribadian dalam Meningkatkan Loyalitas Merek Disney+Hotstar di Indonesia - Odelia, Franciska; Madeline, Victoria; Joseph Wibowo, Alexander Ibnu; Yudianto, Bernadinus Realino (Universitas Prasetiya Mulya, 2024)
This study analyzes the influence of personality on consumer benefits, perceived quality, and brand loyalty of Disney+ Hotstar in Indonesia. In addition, this study also analyzes the effect of consumer benefits and perceived quality on Disney+ Hotstar’s brand loyalty in Indonesia. This research methodology uses a quantitative methodology where researchers collected data from 388 respondents and processed using the statistical programs SPSS 27 and AMOS 26. This research proves that “excitement” personality influences the